Phase 1b study of obinutuzumab, ibrutinib, and venetoclax in relapsed and refractory chronic lymphocytic leukemia - Rogers, Kerry A. (Blood, 2018)
Targeted therapies including the engineered afucosylated anti-CD20 monoclonal antibody obinutuzumab, Bruton’s tyrosine kinase inhibitor ibrutinib, and B-cell lymphoma protein 2 inhibitor venetoclax have demonstrated significant clinical activity in chronic lymphocytic leukemia (CLL) and, based on their complementary mechanisms, are ideal for combination. However, combining venetoclax with other active agents raises safety concerns, as it may increase the risk for tumor lysis syndrome. To minimize this risk, we designed and implemented a fixed-duration regimen using sequentially administered obinutuzumab followed by ibrutinib (cycle 2) and venetoclax (cycle 3), for a total of fourteen 28-day cycles. This phase 1b study included 12 patients with relapsed or refractory CLL. We tested 3 dose levels of venetoclax and identified the doses of all 3 agents approved by the US Food and Drug Administration for use in the combination. Adverse events were consistent with known toxicities of the individual agents, with hematologic adverse events being most frequent. No clinically significant tumor lysis syndrome occurred. The overall response rate was 92% (95% confidence interval, 62%-100%), with 42% (5/12) achieving a complete remission or complete remission with incomplete marrow recovery. There were 6 patients with no detectable CLL in both the blood and bone marrow at the end of treatment. We found this regimen to be safe and tolerable in CLL, and capable of inducing deep responses, justifying future study in our ongoing phase 2 cohorts of relapsed or refractory and treatment-naive patients, as well as larger phase 3 trials currently in planning. This trial was registered at www.clinicaltrials.gov as #NCT02427451.